ANALISIS FONETIK BAHASA BUGIS DIALEK BARRU: CERITA LA PESOK SIBAWA LABUTA (Phonetic Analysis of Buginese Language of Barru Dialect: Story of La Pesok sibawa La Buta) - Herianah Herianah (SAWERIGADING, 2009)
This writing discusses concerning phonetic analysisof Buginese Language of Barru dialect. Phonetic analysis is intended to investigate and to analyze pronouncing sounds produced by human articulator. Method used in this writing is descriptive. In the first part of discussion, the writer makes transliteratoin the story of La Pesok sibawa La Buta. Furthermore, phonetic is done in addition to clarify sound bases on phonetic analysis, description of vowel and consonant illustration in the word and making map is of vowel and consonant sound.